Outcomes of RestoreX Penile Traction Therapy in Men with Peyronie's Disease: Results from Open Label and Follow-Up Phases. Issue 12 (20th November 2020) - Joseph, Jason; Ziegelmann, Matthew J.; Alom, Manaf; Savage, Joshua; Köhler, Tobias S.; Trost, Landon
Abstract: Background: A randomized, controlled clinical trial evaluating the efficacy of RestoreX traction therapy in men with Peyronie's disease (PD) has been completed, with the 3-month results previously reported. The present study presents outcomes from the open-label and follow-up phases of the original trial. Aim: To report 6-month (open-label phase) and 9-month (follow-up phase) outcomes from a randomized, controlled trial (NCT03389854 ). Methods: A randomized controlled trial was performed from 2017 to 2019 in 110 all-comer men with PD. Men were randomized 3:1 to RestoreX (PTT) or no therapy (control) for 3 months, followed by 3-month open-label and follow-up phases. Key outcomes included adverse events (AEs), changes in penile curvature and length, erectile function, and standardized and nonstandardized assessments of PD. Outcomes: The primary outcomes are safety, penile length, penile curvature, Peyronie's Disease Questionnaire, International Index of Erectile Function, and satisfaction. Results: 6-month (n = 64) and 9-month (n = 63) outcomes were reported, with a mean duration of PTT use of 31.1 minutes. No significant AEs were reported, with temporary erythema and discomfort being most common and resolving within minutes. On intent-to-treat analysis, control-to-PTT men experienced significant length (1.7–2.0 cm) and curvature improvements (18–20%). PTT-to-PTT men also achieved additional length (0.6–0.8 cm) without further curvature improvements. An as-treated analysis of PTT use ≥15 minute/day demonstrated 2.0- to 2.3-cm length gains (largest of any PTT to date) and 18–21% curve improvement. All sexual function domains of the International Index of Erectile Function and Peyronie's Disease Questionnaire were significantly improved (except orgasmic domain). 95% of men treated for 6 months experienced length gains (mean 2.0–2.2 cm), and 61% had curve improvements (16.8–21.4° [32.8–35.8%]). RestoreX was preferred 3–4:1 over all other PD treatments, and 100% preferred it over other PTT devices. Clinical Implications: Use of RestoreX 30 minutes daily results in significant length and curve improvements in PD men without significant AEs. Strengths & Limitations: Strengths include largest randomized study of PTT, blinded assessments, and inclusion of all-comers with few restrictions; limitations include sample size that precludes comparisons between treatment cohorts and lack of long-duration (>3–9 hours) treatment arm. Conclusion: PTT with RestoreX results in significant improvements in length, curve, and subjective and objective measures of sexual function without significant AEs. RestoreX PTT represents a safe, conservative, low-cost option for managing men with PD.